Trait-level predictors of human performance outcomes in personnel engaged in stressful laboratory and field tasks - Brunyé, Tad T.; Goring, Sara Anne; Cantelon, Julie A.; Eddy, Marianna D.; Elkin-Frankston, Seth; Elmore, Wade R.; Giles, Grace E.; Hancock, Clifford L.; Masud, Shoaib Bin; McIntyre, James; McKenzie, Kari L.; Mitchell, K. Blake; et al. (Frontiers in Psychology, 2024)
Personnel performance under stress hinges on various factors, including individual traits, training, context, mental and physiological states, and task demands. This study explored the link between the traits of military personnel and their performance outcomes in five domains: move, shoot, communicate, navigate, and sustain. A total of 387 U.S. Army soldiers participated in this study, undergoing trait assessments covering physical, cognitive, social-emotional, demographic/lifestyle, and health domains. Performance was measured through lab and field events assessing a broad range of individual and team-level skills under conditions demanding resilience to acute cognitive and physical stress exposure. Analysis used feature selection and elastic net regression, and revealed complex associations between traits and performance, with physical, cognitive, health-related, social-emotional, and lifestyle traits playing roles in guiding and constraining performance. Measures of resilience, emotion regulation, grit, and mindfulness were identified as relevant predictors of several performance-related outcomes. Results carry implications for the selection, training, and operational effectiveness of personnel in high-stakes occupations including military and first response. Further research is necessary to explore the mechanisms underlying these associations and inform targeted interventions to boost personnel effectiveness.